Prostatosymphyseal Fistula Treated by Robotic Assisted Radical Prostatectomy - Lucy Whelan; Emma Mullarkey; Henry H. Woo (Case Reports in Urology)
This case report documents a rare complication of prostate resection following a Greenlight laser procedure. The 75-year-old gentleman involved underwent photoselective vaporisation of the prostate (PVP) for clinically benign prostatic obstruction. Subsequent to PVP, the patient experienced recurrent macroscopic haematuria and pubic pain. Investigations confirmed the presence of a prostate-symphyseal fistula, a rare complication of PVP. We believe this to be the first reported case of successful treatment with robotic assisted radical prostatectomy.